SALAI JIN COMMUNICATION RITUAL IN THE ISLAND TIDORE COMMUNITY - Rakhmat Rakhmat; Muhammad Najmuddin (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
Salai Jin is a dance that is believed to have magical powers and is used by the community as a ritual to connect the human realm with the Jinn realm. This dance which contains mystical rituals is performed to ask for help from the Jinn, such as; healing the sick, repelling the plague, or as a form of benefit if the ritual succeeds in healing the sick. This research uses descriptive-qualitative analysis with the Ethnographic Communication approach. Data collection is done directly by the researcher. This technique is carried out using question and answer interaction with or without using interview guidelines with traditional leaders, ritual implementers, and researchers who have conducted Salai Jin studies. Salai Jin or the genie dance is a ritual communication process carried out by the Tidore Islands community with the aim of being able to establish relationships with the jinn nation which is called the embodiment of the ancestors or Papa se Tete so that the Jinn can provide assistance to heal one of the residents of the disease suffered. In general, this ritual procession takes place inside and outside the room led by Sowohi or traditional elders.